2010
DOI: 10.1038/sj.bjc.6605804
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific exposure prevalence of established risk factors for oesophageal adenocarcinoma

Abstract: Background:There is an unexplained male predominance in the incidence of oesophageal adenocarcinoma, and the sex-specific distribution of its risk factors in the general population is not known.Methods:A random sample of Swedish citizens aged 40–79 years completed a questionnaire for assessment of the prevalence of five risk factors for oesophageal adenocarcinoma: reflux symptoms, body mass index, tobacco smoking habits, socioeconomic status, and use of non-steroidal anti-inflammatory drugs (NSAIDs). Logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 45 publications
0
24
1
1
Order By: Relevance
“…Fourteen articles were excluded because of overlap, and 15 articles did not give data on sexspecific prevalence (n = 13) or dealt with single sex population only (n = 2). Fifteen studies were conducted in Asia [2,[29][30][31][32][33][34][35][36][37][38][39][40][41][42], 14 were conducted in Europe [1,10,[43][44][45][46][47][48][49][50][51][52][53][54], and five studies were from the US [55][56][57] and South America [58]. Studies included data on 301 705 patients with significantly more women with 54.5 ± 1.4% (range: 32.1-74.6%; P < 0.001).…”
Section: Sex and Reflux Symptomsmentioning
confidence: 99%
“…Fourteen articles were excluded because of overlap, and 15 articles did not give data on sexspecific prevalence (n = 13) or dealt with single sex population only (n = 2). Fifteen studies were conducted in Asia [2,[29][30][31][32][33][34][35][36][37][38][39][40][41][42], 14 were conducted in Europe [1,10,[43][44][45][46][47][48][49][50][51][52][53][54], and five studies were from the US [55][56][57] and South America [58]. Studies included data on 301 705 patients with significantly more women with 54.5 ± 1.4% (range: 32.1-74.6%; P < 0.001).…”
Section: Sex and Reflux Symptomsmentioning
confidence: 99%
“…However, this difference has not been totally attributed to the known risk factors because Barrett's epithelium, low socioeconomic status, and alcohol and tobacco consumption cannot adequately explain this marked sex difference (Chandanos and Lagergren, 2009;Rashid et al, 2010). It has been hypothesized that hormonal factors might play a role in the aetiology of oesophageal cancer (Mao et al, 2011), which has been supported by several basic studies that have shown that oestrogen may have inhibitory effects on the growth of oesophageal cancer cells (Lagergren and Nyrén, 1998;Chandanos and Lagergren, 2009;Rutegård et al, 2010;Yang et al, 2012). Nevertheless, few studies on oesophageal cancer have provided strong enough evidence to support this protective effect.…”
Section: Introductionmentioning
confidence: 94%
“…Aufgrund der unterschiedlichen Effektstärken dieser Einflussfaktoren auf die Geschlechter und einer eher weiblichen Ausprägung werden diese nicht einheitlich als unabhängige Risikofaktoren bewertet [8,14]. Ein Grund die Risikofaktoren getrennt nach dem Geschlecht zu erfassen (l " Abb.…”
Section: öSophaguskarzinomunclassified